Pathways toward Jihadism in Western Europe: An Empirical Exploration of a Comprehensive Model of Terrorist Radicalization - Pfundmair, Michaela; Aßmann, Elena; Kiver, Benjamin; Penzkofer, Maximilian; Scheuermeyer, Amelie; Sust, Larissa; Schmidt, Holger (Terrorism and political violence, 2022)
Islamist terror is one of the most terrifying threats worldwide. However, there is no common model about the mechanisms underlying the complex process of radicalization and research is usually undermined by a lack of empirical data. Therefore, we aimed to compose a comprehensive model of radicalization, and test it empirically collecting and analyzing data on Islamist radicals in Western Europe. In Study 1, police professionals assessed seventy-five subjects under investigation for being in the process of radicalization. In Study 2, data from open source news articles about eighty six radical Muslims were evaluated by psychologists. Specific individual preconditions including young age, male gender, migration background, and biographical cuts were consistently found among radicals. Fueling the actual radicalization process, a gradual increase of individual, group and catalyst processes was observed from early (Study 1) to late stages of radicalization (Study 2). These included pursuing individual needs (transcendence, significance, self-esteem, control); processes in the course of a strong group commitment (group identification, prejudice, polarization, perceived group threat, collective emotions, informative influence); and cognitive adaptions to get increasingly comfortable with applying violence (desensitization, dehumanization). The current work may be a solid basis for further empirical investigations and for creating means of prevention and deradicalization.